1978
DOI: 10.1007/bf00237602
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of receptive field responses and shift-effect in cat retinal and geniculate neurons

Abstract: Spike activity of single optic tract fibres and lateral geniculate cells of the lightly anaesthetized immobilized cat were recorded in response to short, small (local) test flashes into the receptive field center before, during and after rapid displacements of a remote, large (global) pattern. 2. The majority of retinal and geniculate neurons failed to produce algebraic summation of the excitatory shift-effect and an excitatory test response. 3. For many cells outside lamina A and A1 of the dorsal lateral geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Although Y cells in the lateral geniculate nucleus did have a prominent shift effect, we found little evidence for interaction between peripheral stimuli and stimuli delivered to the receptive field in either X or Y cells. However, in a study simultaneous with ours, Fischer, Barth & Sternheim (1978) 361 362 A. M. DERRINGTON AND A. F. FUCHS also presented shift effect stimuli at different times relative to adequate stimuli delivered to the receptive field. In no identified cells in layers A andAl did the responses to the two stimuli interfere, and in only 3/11 cells was there partial rather than complete summation of the responses (their Fig.…”
Section: Properties Of X and Y Neuroses In The Lateral Geniculate Nucmentioning
confidence: 48%
See 1 more Smart Citation
“…Although Y cells in the lateral geniculate nucleus did have a prominent shift effect, we found little evidence for interaction between peripheral stimuli and stimuli delivered to the receptive field in either X or Y cells. However, in a study simultaneous with ours, Fischer, Barth & Sternheim (1978) 361 362 A. M. DERRINGTON AND A. F. FUCHS also presented shift effect stimuli at different times relative to adequate stimuli delivered to the receptive field. In no identified cells in layers A andAl did the responses to the two stimuli interfere, and in only 3/11 cells was there partial rather than complete summation of the responses (their Fig.…”
Section: Properties Of X and Y Neuroses In The Lateral Geniculate Nucmentioning
confidence: 48%
“…Although Y cells in the lateral geniculate nucleus did have a prominent shift effect, we found little evidence for interaction between peripheral stimuli and stimuli delivered to the receptive field in either X or Y cells. However, in a study simultaneous with ours, Fischer, Barth & Sternheim (1978) Ikeda & Wright (1976) and Cleland et al (1971). Rather than measuring corner frequency, other authors (Ikeda & Wright, 1976;Hoffinann & Sireteanu, 1977) (1971) found that responses of lateral geniculate neurones were less sustained than retinal responses, and that several other properties had to be examined before a cell could be conclusively classified as either sustained or transient.…”
Section: Properties Of X and Y Neuroses In The Lateral Geniculate Nucmentioning
confidence: 92%
“…We have checked that, on its own, the shift also increases the firing rate of the majority of retinal ganglion cells. We are testing a number of possible explanations for the difference in effect between the shift stimuli used in our experiments and the shift stimuli used in previous papers (Fischer et al, 1978;Derrington et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The retinal shift effect, elicited by stimulation outside the conventional receptive field, is of excitatory nature (Mcllwain, 1964;Fischer, Kruger & Droll, 1975;Fischer, Barth & Sternheim, 1978). Similar excitatory responses are observed in cells of the dorsal lateral geniculate nucleus (d.l.g.n.)…”
Section: Introductionmentioning
confidence: 91%
“…Similar excitatory responses are observed in cells of the dorsal lateral geniculate nucleus (d.l.g.n.) following rapid displacements of patterns in the peripheral visual field, but with appropriate steady illumination of the receptive field, decreases in activity are found as well (Fischer & Kruger, 1974;Fischer et al 1978). Differences present between X-and Y-cell shift effects in the retina (Hamasaki & Hanada 1983; equal peak rates but larger shift-response amplitudes in Y than in X cells) are more pronounced in d.l.g.n.…”
Section: Introductionmentioning
confidence: 96%